HANDLING STANDARD OPERATING PROCEDURE EXPORT DOCUMENT OCEAN FREIGHT - Ricardianto, Prasadja; Setiawan, Agus; Pujianto, Agus (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
PT Schenker Petrolog Utama is one of the most prominent companies in Indonesia that handle service in domestic cargo delivery. In analyzing the problems in handling Standard Operating Procedure (SOP) especially for export documents, the author uses a tree analysis consisting of problem tree, target tree, and alternative tree. The first analysis is done in the process of handling export documents. After that, analysis on the root of problem in handling export documents by using questionnairesâit successfully identifies four problems: lack of human resources, poor communication among the employees in handling export documents, computer network system which is in problem, and slow response from the customer to confirm the export documents. Subsequently, analysis on the solutions or alternative actions for those problems in handling export documents.